2019
DOI: 10.1021/acs.jpcb.9b04617
|View full text |Cite
|
Sign up to set email alerts
|

Short-Range Structure, Thermal and Elastic Properties of Binary and Ternary Tellurite Glasses

Abstract: Glasses Al2/3O–TeO2, ZnO–TeO2 and R2/3O–ZnO–TeO2 (R = Al, B) were prepared by melting in Pt crucibles and studied for correlations between structure and thermal as well as mechanical properties, whereby the glass composition is varied to tailor the short-range speciation of tellurite, aluminate, and borate groups. The glass structure was studied by Raman and infrared spectroscopy analyses, and the measured properties include glass-transition temperature (T g), density (ρ), and ultrasonic longitudinal (V L) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…For radii we use effective ionic radii of Shannon, 88 taking the values r O = 1.35 Å for oxygen and r Bi = 1.03 Å for bismuth, the latter corresponding to Bi in six-fold coordination. For the ionic radius of boron we take into consideration the change in coordination number with composition (x) and write r B = X 4 r B(4) + (1 À X 4 )r B(3) , 89 where the boron ionic radii for 4-and 3-fold coordination are r B(4) = 0.11 Å and r B(3) = 0.01 Å; 88 recognizing though that boron has a very small effect on C g in comparison to oxygen and bismuth. The calculated C g values are given in Table 3, while the evolution of the atomic packing density with composition is demonstrated in Fig.…”
Section: Property-structure Correlations In Bismuth-borate Glassesmentioning
confidence: 99%
“…For radii we use effective ionic radii of Shannon, 88 taking the values r O = 1.35 Å for oxygen and r Bi = 1.03 Å for bismuth, the latter corresponding to Bi in six-fold coordination. For the ionic radius of boron we take into consideration the change in coordination number with composition (x) and write r B = X 4 r B(4) + (1 À X 4 )r B(3) , 89 where the boron ionic radii for 4-and 3-fold coordination are r B(4) = 0.11 Å and r B(3) = 0.01 Å; 88 recognizing though that boron has a very small effect on C g in comparison to oxygen and bismuth. The calculated C g values are given in Table 3, while the evolution of the atomic packing density with composition is demonstrated in Fig.…”
Section: Property-structure Correlations In Bismuth-borate Glassesmentioning
confidence: 99%
“…They demonstrated that tellurite glasses are fragile even from the viewpoint of mechanical properties because of their weak bond strengths and open atomic packing structures . Tagiara et al showed recently that the mechanical properties of ZnO‐TeO 2 glasses could be improved by introducing B 2 O 3 (eg, x B 2 O 3 ‐(30 − x )ZnO‐70TeO 2 , 0 ≦ x ≦ 30) that leads to increased bonding strength and to larger packing density of the glass network. The combination of B 2 O 3 (the acidic oxide and low electronic polarizability) and TeO 2 (the basic oxide and high electronic polarizability) is a good design for improving poor mechanical properties of TeO 2 ‐based glasses.…”
Section: Approach To Unique Properties Of Teo2‐based Glassesmentioning
confidence: 99%
“…Especially in the field of oxide glasses, the thermodynamic model of Shakhmatkin and Vedishcheva has been successfully applied in previous years. [1][2][3][4][5][6][7][8][9] The SVTDM model considers glasses and melts to be an ideal solution formed by salt products of equilibrium chemical reactions of simple starting substances, e.g. oxides, halides, etc.…”
Section: Shakhmatkin and Vedishchevamentioning
confidence: 99%
“…In recent years, the effect of the crucible material on glass composition, structure and, subsequently, the glass thermal, electrical and mechanical properties has attracted increasing attention in glass chemistry and physics [1][2][3][4][5][6][7]. Especially, the dissolution of alumina crucibles was shown to modify phosphate, silicate or tellurite networks through addition of Al 2 O 3 leached from the crucible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation